The Synod of Dordt (1618-1619) and the canons: historical perspectives - Sinnema, Donald (Reformed historical-theological studies, 2025)
"A scholarly study of one of the most significant meetings of the Reformed tradition, the Synod of Dordrecht (1618-1619)"-- Provided by publisher